Anxiety and anxiety sensitivity as predictors of fear of childbirth: different patterns for nulliparous and parous women - Jokić-Begić, Nataša (Array, 2014)
The demographic characteristics, maternal parity and personal traits of pregnant women have been frequently studied predictors of fear of childbirth (FOC). The aim of this study was to examine the role of demographic variables, expected pain level, trait anxiety and anxiety sensitivity in FOC among nulliparous and multiparous women in the last trimester of pregnancy. Two-hundred pregnant women completed a booklet with questionnaires including the Wijma Delivery Expectancy/Experience Questionnaire (W- DEQ), Anxiety Sensitivity Index (ASI), The State – Trait Anxiety Inventory (STAI) and questions on expected labor pain and demographics. Results showed that FOC was higher amongst nulliparous women, but FOC level was not associated with other demographic variables. Different predictors were established in nulliparous and multiparous women. While higher intensity of expected labor pain and anxiety sensitivity (dimension physical concern) were significant predictors in both groups, trait anxiety was significant for the first-time mothers only. Amongst all women, anxiety sensitivity (physical concerns dimension) was identified as an important vulnerability factor for FOC. As such, the level of anxiety sensitivity, and any resulting fear or expectations of pain, should be assessed in expectant mothers by clinicians in prenatal settings. Furthermore, anxiety sensitivity should be an important target for psychological interventions aimed at managing FOC. {ENG]